On distance-regular graphs and (s,c,a,k)-graphs - Bautista, Lincoln A. (Animo Repository, 1998)
This thesis is an exposition of the paper of Paul Terwilliger entitled Distance-Regular Graphs and (s, c, a, k)-Graphs . In this paper, the following are presented: 1. A diameter bound theorem for a class of distance-regular graphs which includes all those with even girth. 2. A new class of graphs, called (s, c, a, k)-graphs, which are conjectured to contain enough of the local structure of finite distance-regular graphs for them to be all finite. 3. A (s, c, a, k)-graph is finite and a bound on the diameter is given if a - c.